Minority ethnic pupils in the longitudinal study of young people in England (Extension report on performance in public examinations at age 16) - Strand, S (Department for Education, 2008)
Strand (2007) reported an analysis of the LSYPE Wave 1 data, specifically linked to the pupils’ attainment in Key Stage 3 (KS3) national tests in 2004. However, the end of KS3 (age 14) represents an intermediate stage in secondary education, just over halfway through the secondary phase. In contrast to KS3 tests, public examinations at age 16 are ‘high stakes’ examinations that have a direct impact on pupils’ employment prospects and/or entry to further education. There is evidence that many ethnic groups make stronger educational progress during Key Stage 4 (KS4) than they do during KS3 (Strand, 2006; Demie and Strand, 2006; Wilson et al, 2005). For these reasons this extension was undertaken to consider outcomes at age 16 in 2006, and in particular associations between ethnicity and educational attainment and progress over the entire secondary phase. The report is intended and should be read as an Appendix to the original report (Strand, 2007).